Determinan Kepatuhan Berobat Pasien Hipertensi pada Fasilitas Kesehatan Tingkat I - Liberty, Iche A.; Pariyana, Pariyana; Roflin, Eddy; Waris, Lukman (Pusat Penelitian dan Pengembangan Sumber Daya dan Pelayanan Kesehatan, 2017)
Puskesmas is a First Level Health Facility Until now, the management of non-communicable diseases which is still a big challenge in Puskesmas is hypertension. One effort that can be done to reduce the morbidity rate of hypertension is the consumption of antihypertensive, but still few patients who adhere to this treatment. This study aims to analyze the determinants of adherence in patients undergoing treatment of hypertension and how it affects blood pressure control of hypertensive patients. This research is an observational analytic research with cross sectional approach. This research was conducted in Palembang city from August to October 2017. The samples were patients who went to Puskesmas Karyajaya, Kenten, Plaju, Sei Baung, and Campus which fulfilled the inclusion criteria with a total sample of 90 patients. Data analysis in this research was univariate and bivariate analysis with Chi Square Test. Determinant which influence to adherence in this research was duration of hypertension with POR 0,11 with CI 95% 0,02-0,52 (p value = 0,04). While other determinants of gender, age, education level, occupation, Body Mass Index, BPJS participation, and family history of hypertension have no significant effect on hypertension patient’s treatment compliance. Compliance of patients in undergoing treatment of hypertension is also a determinant that affects the control of blood pressure of respondents. The determinants that affect the adherence in this study are duration of hypertension, thus health workers at first-level facility is very necessary attention to a history of hypertension patients in order to improve therapeutic efficacy.Keyword: Determinan, Adherence, High Blood Pressure